American Women in the Vittel Internment Camp: Religions, Morality, and Culture. Issue 3 (1st December 2019) - Delano, Page Dougherty
Abstract : This article is a study of the complex social environment within the Vittel internment camp in eastern France during World War II. The Germans arrested some two thousand British women and then nearly three hundred American women of different class backgrounds, religions, political beliefs, and national affiliations, who were placed in the hotels of this spa town. The Vittel internment camp also became the temporary home of around three hundred Jews from the Warsaw ghetto, who claimed to possess American and South American citizenship. Most of these Jews were sent to their deaths at Auschwitz. Drawing on memoirs, letters, Red Cross reports, and scattered histories, this article explores the interactions, resistance, and prejudices of camp inhabitants. It argues that American women's behavior was guided less by religious beliefs than one might expect in the context of the 1940s.